Social functioning and socioeconomic changes after introduction of regular dialysis treatment and impact of dialysis modality: A multi‐centre survey of Japanese patients. (August 2015) - Nakayama, Masaaki; Ishida, Mari; Ogihara, Masahiko; Hanaoka, Kazushige; Tamura, Masahito; Kanai, Hidetoshi; Tonozuka, Yukio; Marshall, Mark R
Abstract: Aim: Patient socialization and preservation of socioeconomic status are important patient‐centred outcomes for those who start dialysis, and retention of employment is a key enabler. This study examined the influence of dialysis inception and modality upon these outcomes in a contemporary Japanese cohort. Methods: We conducted a survey of prevalent chronic dialysis patients from 5 dialysis centres in Japan. All patients who had been on peritoneal dialysis (PD) since dialysis inception were recruited, and matched with a sample of those on in‐centre haemodialysis (ICHD). We assessed patients' current social functioning (Short Form 36 Health Survey), and evaluated changes to patient employment status, annual income, and general health condition from the pre‐dialysis period to the current time. Results: A total of 179 patients were studied (102 PD and 77 ICHD). There were no differences in social functioning by modality. Among them, 113 were employed in the pre‐dialysis period with no difference by modality. Of these, 22% became unemployed after dialysis inception, with a corresponding decline in average working hours and annual income. The odds of unemployment after dialysis inception were 5.02 fold higher in those on ICHD compared to those on PD, after adjustment for covariates. There were no changes for those who were already unemployed in the pre‐dialysis period. Conclusions: Employment status is significantly hampered by dialysis inception, although PD was associated with superior retention of employment and greater income compared to ICHD. This supports a positive role for PD in preservation of socioeconomic status and potentially other patient‐centred outcomes. Summary at a Glance: This study looked at the socioeconomic outcomes in patients who are started on renal replacement therapy in Japan. It also compared the effect that differing dialysis modality has on these outcomes and suggested a superior effect of peritoneal dialysis.